2020
DOI: 10.1021/acs.chemmater.0c01676
|View full text |Cite
|
Sign up to set email alerts
|

Side Chain Regioisomers that Dictate Optical Properties and Mechanofluorochromism through Crystal Packing

Abstract: Designing strong interactions into π-conjugated materials can direct their typically uncontrolled molecular packing and is an important strategy toward tuning their technologically relevant properties in the solid state. Here we demonstrate unconventional control over solid-state fluorescence and mechanofluorochromism (MFC) through regiochemical substitutions in side chains of 12 three-ring phenylene ethynylenes (PEs) that employ fluoroarene–arene (ArF–ArH) interactions between tetrafluoro ArF pendants and PE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 86 publications
1
17
0
Order By: Relevance
“…In the 1 H NMR spectrum, we observed separate signals of the E and Z conformers at room temperature; however, these signals were coalesced at 45 °C in tetrachloroethane-d 2 . The Z conformer was the favoured conformer in solution, which was determined using 1 H- 19 F heteronuclear Overhauser spectroscopy (HF HOESY) spectra (see the ESI †). The free energy difference of 3HCl between the E and Z conformers was comparable to that of 3tfa, 11 and ΔΔG°, which is the difference of free energy of the E and Z conformers before and after the addition of acid, was 1.16 kcal mol −1 at −40 °C (calibrated to 236 K) in CD 2 Cl 2 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the 1 H NMR spectrum, we observed separate signals of the E and Z conformers at room temperature; however, these signals were coalesced at 45 °C in tetrachloroethane-d 2 . The Z conformer was the favoured conformer in solution, which was determined using 1 H- 19 F heteronuclear Overhauser spectroscopy (HF HOESY) spectra (see the ESI †). The free energy difference of 3HCl between the E and Z conformers was comparable to that of 3tfa, 11 and ΔΔG°, which is the difference of free energy of the E and Z conformers before and after the addition of acid, was 1.16 kcal mol −1 at −40 °C (calibrated to 236 K) in CD 2 Cl 2 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We elaborated this phenomenon in a systematic study of 12 PE analogs with tetrafluorinated side chains that varied in both the regiochemistry of fluorine substitution (with a single H atom in the 4, 5, or 6 position) and electronic substituent effects in the main chain. 205 Notably, we found that fluorine regiochemistry could either fine-tune optical properties in solids (e.g., 5-hydro solids blue-shifted from 6-hydro isomers) or broadly shift them with the loss of ArF−ArH programmed twisting and inversion of MFC from bathochromic to hypsochromic responses in 4-hydro isomers. These regioisomer effects were attenuated when ArF−ArH stacking was sufficiently strong for all isomers due to main chain electronics (NMe 2 ), accentuated where weaker EDGs would enable regioisomerism to tip the balance between competing interactions, and attenuated again when an EWG substituent (CO 2 Me) rendered ArF−ArH uncompetitive for all side chain regioisomers.…”
Section: ■ Halogen-bonding Interactions: 2dmentioning
confidence: 87%
“…We elaborated this phenomenon in a systematic study of 12 PE analogs with tetrafluorinated side chains that varied in both the regiochemistry of fluorine substitution (with a single H atom in the 4, 5, or 6 position) and electronic substituent effects in the main chain . Notably, we found that fluorine regiochemistry could either fine-tune optical properties in solids (e.g., 5-hydro solids blue-shifted from 6-hydro isomers) or broadly shift them with the loss of ArF–ArH programmed twisting and inversion of MFC from bathochromic to hypsochromic responses in 4-hydro isomers.…”
Section: Interactions Of Aromatic Rings: Tunable Stacking and Dynamic...mentioning
confidence: 98%
“…The structural refinements were carried out using Shelxl-2018. 27 The positions of all the atoms were obtained using direct methods, and the crystallographic details are summarized in Table S1 .…”
Section: Methodsmentioning
confidence: 99%